Livestock Epigenetics 2011
DOI: 10.1002/9781119949930.ch4
|View full text |Cite
|
Sign up to set email alerts
|

Sheep as an Experimental Model for Human ART: Novel Insights on Phenotypic Alterations in ART‐Derived Sheep Conceptuses

Abstract: For those organizations that have been granted a photocopy license by CCC, a separate system of payments has been arranged. The fee codes for users of the Transactional Reporting Service are ISBN-13: 978-0-4709-5859-9/2012. Designations used by companies to distinguish their products are often claimed as trademarks. All brand names and product names used in this book are trade names, service marks, trademarks or registered trademarks of their respective owners. The publisher is not associated with any product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 651 publications
(888 reference statements)
0
1
0
Order By: Relevance
“…Moreover, comparative transcriptomic analyses of oocytes of different species have revealed that the bovine-human similarity is greater than mouse-human similarity (Sylvestre et al, 2013). Also, a number of recent studies have demonstrated close similarities between human and sheep embryos in metabolism and key stages before and after implantation development (Barry and Anthony, 2008;Loi et al, 2011;McMillen, 2001), and correspondingly, it is suggested that the sheep is an relevant experimental model for human assisted reproduction techniques (Loi et al, 2011). Therefore, we have used sheep as an animal model to evaluate the fundamental aspects of oocyte cryobiology in human (Asgari et al, 2011(Asgari et al, , 2012a(Asgari et al, , 2012bHosseini et al, 2012Hosseini et al, , 2015aHosseini et al, , 2015b.…”
Section: Are Mice Relevant Models For Human Oocyte Vitrification?mentioning
confidence: 99%
“…Moreover, comparative transcriptomic analyses of oocytes of different species have revealed that the bovine-human similarity is greater than mouse-human similarity (Sylvestre et al, 2013). Also, a number of recent studies have demonstrated close similarities between human and sheep embryos in metabolism and key stages before and after implantation development (Barry and Anthony, 2008;Loi et al, 2011;McMillen, 2001), and correspondingly, it is suggested that the sheep is an relevant experimental model for human assisted reproduction techniques (Loi et al, 2011). Therefore, we have used sheep as an animal model to evaluate the fundamental aspects of oocyte cryobiology in human (Asgari et al, 2011(Asgari et al, , 2012a(Asgari et al, , 2012bHosseini et al, 2012Hosseini et al, , 2015aHosseini et al, , 2015b.…”
Section: Are Mice Relevant Models For Human Oocyte Vitrification?mentioning
confidence: 99%